QSLB: queue size based single path load balancing routing protocol for MANETs. (2017) - Naseem, Mohd; Kumar, Chiranjeev
A mobile ad hoc networks (MANETs) is a collection of independent mobile nodes, which are able to communicate in the wireless medium without the assistance of any infrastructure. Because of the dynamic nature of MANETs and resources constraints of wireless medium, load must be distributed throughout the network based on some parameters. Otherwise, resources of the heavily loaded nodes deplete soon and those nodes could not participate further in the communication. So, network performance degrades due to the congestion. Load at the nodes situated in the centre of the network is higher as compared to the other part of the network. In this paper, we propose a load balancing technique that distributes the traffic throughout the network in such a way that load at the centre of the network decreases. Simulation results show that the proposed routing protocol distributes the load efficiently and improve the network performance.